COMPUTERIZED FACILITIES LAYOUT DESIGN - Mulugeta, Ameha; Beshah, Birhanu; Kitaw, Daniel (Zede Journal of Ethiopian Engineers and Architects, 2023)
Facilities are crucial as they usually represent the largest and the most expensive assets of an organization. Determining location of machines, workstations, and other facilities are layout problems in a manufacturing plant. Different computerized algorithms have been developed to optimize the flow of materials within a factory. Among others, CRAFT has been developed to improve an already existing layout while algorithms such as CORELAP are used to build new layouts from scratch. This paper hypothesized that better result could be gained by federating these two algorithms rather than their independent applications. The hypothesis is verified by taking layout problems of Kotebe Metal Tools Factory (KMTF). The result obtained by improving the already existing layout using CRAFT is compared with the result obtained through newly developed layout by CORELAP followed by improving it with CRAFT. From the comparison, this study concluded that federated use of computerized layout design algorithms provides better result.